2015
DOI: 10.3892/mmr.2015.4066
|View full text |Cite
|
Sign up to set email alerts
|

LOX-1 is implicated in oxidized low-density lipoprotein-induced oxidative stress of macrophages in atherosclerosis

Abstract: Abstract. Induction of oxidative stress has a causal role in atherosclerosis. The aim of the present study was to examine the role of lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) in oxidized low-density lipoprotein (OxLDL)-induced oxidative stress in atherosclerosis. Small interfering RNA (siRNA) technology was employed to decrease the expression of LOX-1 in mouse RAW264.7 macrophages and the effects of LOX-1 silencing on OxLDL-induced reactive oxygen species (ROS) generation and NADPH oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 25 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Increase in proatherogenic stimuli such as ox‐LDL, high sensitivity C‐reactive protein (CRP), and homocysteine leads to overexpression of LOX1 in atherosclerotic lesions (Gao & Geng, ). In human studies, it has been proved that there are a close association between LOX1 expression and ROS generation in human vascular smooth muscle cells and macrophages (Dai et al, ; Yang et al, ). Recent finding demonstrated that dietary antioxidants could prevent the ox‐LDL and tumor necrosis factor‐α (TNF‐α)‐induced LOX1 expression and oxidative stress, key events that lead to mitogen‐activated protein kinase/extracellular signal‐regulated kinase (ERK)1/2 and NF‐κB activation linked to endothelial dysfunction (Caliceti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in proatherogenic stimuli such as ox‐LDL, high sensitivity C‐reactive protein (CRP), and homocysteine leads to overexpression of LOX1 in atherosclerotic lesions (Gao & Geng, ). In human studies, it has been proved that there are a close association between LOX1 expression and ROS generation in human vascular smooth muscle cells and macrophages (Dai et al, ; Yang et al, ). Recent finding demonstrated that dietary antioxidants could prevent the ox‐LDL and tumor necrosis factor‐α (TNF‐α)‐induced LOX1 expression and oxidative stress, key events that lead to mitogen‐activated protein kinase/extracellular signal‐regulated kinase (ERK)1/2 and NF‐κB activation linked to endothelial dysfunction (Caliceti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive production of ROS occurs in response to ox‐LDL treatment. However, LOX‐1 siRNA attenuates NADPH oxidase activity and MAPK pathway–dependent ROS production . LOX‐1 also inhibits macrophage migration and promotes foam cell formation induced by various proatherogenic treatments .…”
Section: Cellular and Molecular Mechanisms Of Lox‐1 In Atherosclerosismentioning
confidence: 99%
“…2B). The interaction between oxidized (ox)-LDL and LOX-1 results in ox-LDL uptake by macrophages and foam cell transformation (24,25). Collectively, these results indicate that sarpogrelate and rosuvastatin can synergistically prevent aortic damage induced by hyperlipidemia and reverse atherosclerosis, which may be associated with the regulation of LOX-1 expression.…”
Section: Resultsmentioning
confidence: 87%